KERANGKA ADVOKASI KOALISI DALAM KEBIJAKAN KENAIKAN TARIF CUKAI ROKOK DI INDONESIA - Friska Prastya Harlis (Responsive, 2022)
Permasalahan tarif cukai rokok menjadi semakin kritis karena keadaan ekonomi yang mengalami inflasi akibat pandemic covid sehingga industri rokok kian terancam. Namun disisi lain terdapat harapan untuk membatasi konsumsi rokok agar kesehatan masyarakat terjaga. Tujuan penelitian ini untuk menggambarkan bagimana kerangka koalisi dibentuk dan bagaimana koalisi mengelola beliefs system, resources, dan strategy mereka. Untuk menjawab pertanyaan tersebut, penelitian ini dikawal oleh teori Advocacy Coalition Framework (ACF) dari Sabatier dan Jenkins Smith. Metodologi yang digunakan menggunakan penelitian kualitatif dengan data sekunder. Hasil penelitian menunjukkan bahwa terdapat dua koalisi dalam kenaikan tarif CHT, mereka adalah koalisi pendukung tarif CHT naik, dan penolak tarif CHT naik. Tokoh utama koalisi pendukung tarif CHT naik adalah Kemenkes sedangkan koalisi penolak tarif CHT naik adalah Kemenperin.The problem of cigarette excise rates is becoming increasingly critical due to the economic situation which is experiencing inflation due to the covid pandemic so that the cigarette industry is increasingly threatened. However, on the other hand, there is hope for limiting cigarette consumption so that public health is maintained. The purpose of this study is to describe how the coalition framework is formed and how the coalition manages beliefs systems, resources, and strategies. To answer this question, this research was guided by the theory of the Advocacy Coalition Framework (ACF) from Sabatier and Jenkins Smith. The methodology used qualitative research with secondary data. The results of the study show that there are two coalitions in the increase in CHT rates, they are coalitions that support the increase in CHT rates, and those who oppose the increase in CHT rates. The main figure in the coalition supporting the increased CHT tariff is the Ministry of Health, while the coalition against the increased CHT tariff is the Ministry of Industry.